Intercropping Urochloa brizantha and sorghum inoculated with Azospirillum brasilense for silage - Nakao, Allan Hisashi [UNESP] (2018)
Livestock performance in the Brazilian Cerrado has been limited by the low availability of good quality fodder, especially during periods of low rainfall. The aim of this study was to evaluate growth and dry matter production in two cultivars of sorghum, inoculated or not with diazotrophic bacteria, and as a monocrop or intercropped with palisade grass under a system of crop-livestock integration. The experiments were carried out in the field in the Cerrado region during the autumn-winter period of 2015 and 2016, on the experimental farm of the Faculty of Engineering at Ilha Solteira, UNESP, in Selviria, in the State of Mato Groso do Sul, Brazil (MS). A randomised complete block experimental design was used in a 2 x 2 x 2 factorial scheme with four replications. The treatments corresponded to two agricultural years (2015 and 2016); the cultivation of dual-purpose grain sorghum, alone or intercropped with palisade grass; with or without inoculation of the sorghum seeds with the bacterium Azospirillum brasilense. The dry matter production of the plant components and plant growth were evaluated for the preparation of silage. Inoculation of sorghum seeds with the bacterium Azospirillum brasilense increases the production of plant dry matter for silage, irrespective of the cultivar or intercrop. Dual-purpose grain sorghum intercropped with palisade grass is a viable agronomic system for producing plant matter for silage during the autumn season.